Analytical Performances of the Novel i-STAT Alinity Point-of-Care Analyzer - Romaric Larcher; Maxence Lottelier; Stephanie Badiou; Anne-Marie Dupuy; Anne-Sophie Bargnoux; Jean-Paul Cristol (Diagnostics, 2023)
Many Point-of-Care devices have been released over the past decade. However, data regarding their analytical performances in real-world situations remains scarce. Herein, we aimed to assess the analytical performances of the i-STAT Alinity system. We conducted an analytical performances study with the i-STAT Alinity device using cartridges CG4+ (pH, Pco2, Po2, lactate, bicarbonate and base excess); CHEM8+ (Na, K, Cl, ionized Ca, urea, creatinine, glucose, hematocrit and hemoglobin) and PT/INR (prothrombin time and international normalized ratio). We assessed the imprecision and compared the results to those obtained on existing instruments in the central laboratory. We found that the within-lab coefficients of variation (CV) were very low (<2%) or low (2–5%), except for creatinine and PT (CV = 5.2% and CV = 6.3%, respectively). For almost all the parameters, the results were strongly (R2 = 90–95%) or very strongly (R2 > 95%) correlated with those of the existing laboratory instruments, and the biases were very low (<2%) or low (2–5%). However, correlations of the PT and INR measurements with existing instruments were lower (R2 = 86.0% and 89.7%), and biases in the Po2 (7.9%), creatinine (5.4%) and PT (−6.6%) measurements were higher. The i-STAT Alinity appeared as a convenient device for measurements of numerous parameters. However, clinicians should interpret Po2, creatinine and PT results with caution.